Inventarisasi Dan Peta Sebaran Hama Dan Penyakit Pada Empat Komoditi Unggulan Perkebunan Di Kabupaten Buton, Provinsi Sulawesi Tenggara - luddin, Awa; Botek, Muhammad; Iswandi, Marsuki; Efendi, Siska (Jurusan Budidaya Perkebunan, 2023)
Information on the type of OPT that attacks plantation commodities in Buton Regency is incomplete, even though the data can be the basis for mitigating attacks and controls if the plants have been attacked. For this reason, research was conducted to identify the type and distribution of pests in plantation crops, especially in cocoa, cloves, cashew, pepper, and coconut commodities. They analyzed the damage caused by OPT in plantation crops, especially in cocoa, cloves, cashews, pepper, and coconut commodities, and determined alternative solutions for control and prevention. Observations were made in several villages in several sub-districts in Buton Regency. Direct observations were made on the specified land, and interviews with farmers and various related parties were conducted. To get OPT-type data and damage levels. OPT that attacks cashew consists of two types of pests and one disease. The level of damage OPT in the categorized category of guava plants. The level of damage to the pest on the categorized cashew was low. In coconut commodities, found OPT from three types of pest groups, namely Orycter Rhynocheros, Aspidiotus Destructors, and Pestalotia sp. The level of attack of the three pests was categorized as low. Cocoa was the commodity mainly attacked by OPT, consisting of 4 types of pests and four types of diseases. Fruit rot (Phytophthora palmivora) and stem cancer (Phytophthora palmivora) had a heavy attack rate in all cocoa-producing districts in Buton Regency.